Terapi Tuberkulosis - Melia Sari (Yayasan Pendidikan Medika Indonesia, 2021)
Tuberculosis is an infectious disease caused by the bacteria Mycobacterium tuberculosis. Indonesia is one of the five countries with the highest incidence of tuberculosis cases in the world. Tuberculosis is still a public health problem that causes high morbidity, disability, and death, so it is necessary to make efforts to overcome it. One of the ways to treat tuberculosis is to take the form of both pharmacological and non-pharmacological therapy. The purpose of this paper to determine tuberculosis therapy. The method used is literature research by searching for the words tuberculosis, management, treatment, and Mycobacterium tuberculosis in Google Scholar and Pubmed. Searching the literature from both national and international journals then summarizes the discussion topics and compares the results presented in the articles. From a review of the existing literature, tuberculosis therapies include isoniazid (INH), rifampicin (R), pyrazinamide (Z), ethambutol (E) and streptomish (S). Therapy is tailored to the patient's condition, drug resistance, medication history, and age.